1998
DOI: 10.1007/bf00703452
|View full text |Cite
|
Sign up to set email alerts
|

Stability of different wiring techniques in segmental spinal instrumentation

Abstract: The pullout force of sublaminar and transspinous wires for segmental instrumentation which had been inserted into different segments of human cadaver spines were compared. Four different types of wiring were tested: single and double sublaminar wires, button-wires according to Drummond's technique and button-wires with the additional use of two crimps for each spinous process. A total of 50 tests were performed. In all attempts the bone proved to be the limiting factor. None of the 300 fixed wires failed. Typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Using this technique, Herrera-Soto et al [15] reported a correction of 69% at 2 years follow-up even without associated anterior release. If care is taken not to violate the dome-shaped neural canal when placing intraspinous wires, they obviate the neurologic risks associated with sublaminar wiring [24]. Unfortunately, the resistance to failure by cutout of intraspinous wires is roughly half that of sublaminar wires or laminar hooks [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this technique, Herrera-Soto et al [15] reported a correction of 69% at 2 years follow-up even without associated anterior release. If care is taken not to violate the dome-shaped neural canal when placing intraspinous wires, they obviate the neurologic risks associated with sublaminar wiring [24]. Unfortunately, the resistance to failure by cutout of intraspinous wires is roughly half that of sublaminar wires or laminar hooks [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…If care is taken not to violate the dome-shaped neural canal when placing intraspinous wires, they obviate the neurologic risks associated with sublaminar wiring [24]. Unfortunately, the resistance to failure by cutout of intraspinous wires is roughly half that of sublaminar wires or laminar hooks [23,24]. Soft sublaminar bands distribute the stress over a larger area of bone than sublaminar wires or hooks, theoretically reducing the risk of failure at the device-bone interface [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most rudimentary form of interspinous fixation involves wiring the spinous processes, and the Daab plate and Wilson plate have since been developed [7,9,13]. Spinal instrumentation using the spinous process as an anchor offers limited flexibility [14], but recent studies of lumbar fusion surgery using the Tadpole system and CD Horizon Spire spinous process plate 脪 have shown relatively favorable clinical outcomes [19,41].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that the stability of the constructs is lower in the upper thoracic spine. Heller et al [8] found that the tensile force required to cause failure of constructs using sublaminar wires was significantly lower in upper thoracic spine, progressively increasing in the lower segments. This problem can be overcome by wiring the two most proximal consecutive levels (construct C).…”
Section: Discussionmentioning
confidence: 99%